The integrated, community based approach for farm, market, and diet diversity - Oduor, Francis; Induli, Irene; Jordan, Irmgard; Termote, Céline (2023)
The participatory research approach can be described as a partnership approach to research in which all partners contribute expertise and share decision making as well as responsibilities. This is done to generate highly relevant findings in a manner that is ethical and beneficial to those involved